A Comparative Study of the Positive Cultural Impacts Due to Tourism Development between Urban and Rural Tourist Centres of Kerala: Exploring the Impact of Tourism Development on Cultural Exchange: A Comparative Study between Urban and Rural Tourist Centres of Kerala (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The present study is intended to compare the positive cultural impacts between selected urban and rural tourist centres of Kerala in the light of opinions gathered from the respondents who are the inhabitants of the locality. A total of four hundred respondents are selected for the study out of which 151 are from urban centres and the rest 249 are from rural centres. Five major positive cultural impacts are identified for the study. They are acculturation, preservation of tradition, stimulation of cultural exchange, cultural exchange and fixing cultural identity. From the study it is found that in all the five variables used to measure cultural positives, urban centres are leading over rural.